Evidenced-Based and Institution-Based Self-Knowledge An fMRI Study. (article). - Lieberman, Matthew D.
Behavioral and neuropsychological studies have suggested multiple-self knowledge systems may exist (i. e., evidence-based and intuition-based self-knowledge); however, little is known about the nature of intuition -based knowledge . In a functional magnetic resonance imaging study, the neural correlates of intuition-based and evidence-based self-knowledge were investigated. Participants with high and low experienced in different domains (soccer and acting ) made self descriptiveness judgement about words from each domain while being scanned. High experience domain judgments produced activitation in a networkof neural structures called X-system, involved in automatic social cognition, whereas low experience domain judgement produced activitions in a network called the C-system, involved in effortful social cognition and propositional thought. The affective and slow-changing nature of intuition-based self-knowledge is discussed. -- (from the author). . -- (from the author)